2018
DOI: 10.1017/s0714980818000466
|View full text |Cite
|
Sign up to set email alerts
|

The Unbearable Lightness of Being Retired

Abstract: RÉSUMÉDans cette étude qualitative, j’ai utilisé une approche fondée sur la gérontologie narrative pour examiner les perceptions liées à la retraite dans un groupe de 26 hommes et femmes qui ont pris leur retraite après un mandat de chef de la direction. Le guide d’entrevue a pris en compte la perspective du parcours de vie. Trois thèmes clés ont émergé : 1) l’importance de la productivité et du réseautage, alors que les participants gravissaient les échelons de l’entreprise ; 2) le sentiment d’avoir une date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Olympic athletes are closely scrutinized during their athletic careers, yet often overlooked by society once they retire from their sport. While the participants in this study were by no means ordinary, their athletic retirement experiences reflect a sentiment, typically experienced later in life by nonathletes, that retirement can be a challenging transition that necessitates a recalibration of one's personal identity and social purpose (Silver, 2019). In our excitement to celebrate winning in sports, we often ignore the lessons that can be associated with loss and adaptation to new physical states.…”
Section: Discussionmentioning
confidence: 97%
“…Olympic athletes are closely scrutinized during their athletic careers, yet often overlooked by society once they retire from their sport. While the participants in this study were by no means ordinary, their athletic retirement experiences reflect a sentiment, typically experienced later in life by nonathletes, that retirement can be a challenging transition that necessitates a recalibration of one's personal identity and social purpose (Silver, 2019). In our excitement to celebrate winning in sports, we often ignore the lessons that can be associated with loss and adaptation to new physical states.…”
Section: Discussionmentioning
confidence: 97%
“…Work provided them with a sense of agency, self-efficacy, self-worth, importance, belonging, visibility, appreciation, value, and finally, power and authority. As noted by Herbert 23 and Silver, 24 older adults without major cognitive difficulties also attributed similar value to work activities.…”
Section: Discussionmentioning
confidence: 58%
“…For instance, Herbert 23 found that older rural women continued working because it not only allowed them to maintain financial autonomy but also provided temporal structure to their lives, a sense of purpose, personal agency, and social connectivity. Silver 24 showed that people in executive positions could perceive retirement as an unwanted change forced by social pressure because work provided them with a sense of productivity, networking opportunities, significant fulfillment, and personal satisfaction they did not want to lose. Manor 22 pointed out that the moment of retirement marked the transition to old age and that participants in her study strongly rejected the idea of becoming old.…”
Section: Introductionmentioning
confidence: 99%